La gastronomía ancestral, como potencial turístico de la parroquia Chuquiribamba, cantón Loja - Gutiérrez Tene, Jhoana Cecibel (2024)
The gastronomic tourism that identifies the Chuquiribamba parish, is the way of preparing the products and culinary culture, in this research was proposed as a general objective to promote tourism development of Chuquiribamba, through ancestral cuisine, and two specific objectives: First diagnose the current situation of the ancestral gastronomy of the Chuquiribamba parish, to know the characteristics of the survey of ancestral gastronomic dishes, the author designed cards for the collection of information of each ancestral gastronomic dish , we proceeded to collect information through the card A4 Knowledge and uses related to nature and the adapted universe, of Instituto Nacional de Patrimonio Cultural (INPC), surveys to determine the demand of potential, SWOT analysis and strategic SWOT. Second Objective: Propose strategies for tourism development based on the ancestral gastronomy of the Chuquiribamba parish in the Loja canton. The results and methodology included the taxonomic classification of 12 agricultural products, 10 medicinal plants that make up the horchata drink, 8 ancestral gastronomic dishes, 3 soups, 4 hors d'oeuvres, 1 sango, 4 beverages and 2 desserts, 244 surveys were applied to the PEA (economically active population) of the Loja canton, through the 247 surveys applied to the PEA of the city of Loja, from the matrix of the strategic FODA we obtained 3 strategies that will help for the tourist development of Chuquiribamba. Finally, we were able to establish tourism management strategies linked to ancestral gastronomy to strengthen tourism and local development, improving the quality of life in the parish.